Development of Methods for Effect-Directed Detection and Quantification of Genotoxins and Endocrine Disrupting Chemicals in Complex Matrices - Meyer, Daniel; Justus Liebig University Giessen (My University, 2023)
Consumers, policy makers and industry need more powerful technologies for the detection of genotoxins and endocrine disruptors in complex matrices. Existing methods do not allow the analysis of unknown sample compositions or are based on effect-directed analysis with microorganisms, but this can give false negative results due to cytotoxicity or physico-chemical quenching effects and is not sensitive enough. For the first time, an HPTLC─(S9)-SOS-Umu-C bioassay was developed that also takes into account the metabolic activation of non-genotoxic substances. It was shown that the new bioassay has never reached detection limits. For packaging material migrates, HPTLC was shown to separate genotoxins from the cytotoxic matrix, making them detectable, which was not possible with the SOS-Umu-C microplate bioassay. Genotoxic linolenic acid epoxides were identified by coupling with HRMS. Analysis of several healthy vegetable oils for which the same fatty acid was shown to be a source of genotoxicity, among other genotoxins, showed that air exclusion can reduce genotoxin formation. The pYAES/pYAAS bioassays were used to detect endocrine disruptors in packaging material migrates. For detection enhancement, a 6-fold multiplex assay for simultaneous detection of agonists, antagonists, false positive antagonists, cytotoxins, anti-cytotoxins, and false positive anti-cytotoxins was developed and verified. A packaging agent migrate could be screened for endocrine disruptors and their disruptive properties could be verified in the same bioassay. The bioassays could also be used for risk assessment and authorization procedures under REACH and then improve product safety, as well as save time and costs.
Keywords: Genotoxin; Hochleistungsdünnschichtchromatographie; HPTLC; High-performance thin-layer chromatography; Öl; Verpackungsmittel; Packaging Material; Ames; Umu-C; Metabolic Activation; S9; Bioassay; Verpackungsmaterial; Androgen; Estrogen; Östrogen; YES; YAS; pYES; pYAS; Multiplexassay; ddc:500; ddc:540; ddc:570